PERAN AUDITOR SPESIALISASI INDUSTRI DALAM MENURUNKAN PRAKTIK MANAJEMEN LABA - Ahmad Syifaudin (Universitas Bunda Mulia, 2017)
This study investigates the role of auditor industry specialization (measured by client sales ratio) in mitigating earnings management (measured by discretionary accruals) both before and after regulation no. 17PMK.01/2008 concerning public accountant service issued by Ministry of Financial in Indonesia. The sample is drawn from manufacturing companies which listed in BEI for periods 2006-2009 with a high leverage and size characteristic. This study find evidence that auditor industry specialization have a role in mitigating accrual earnings management better than non industry specialization and auditor industry specialization also have a role in mitigating accrual earnings management at companies with a high leverage and size both before and after this regulation issued.. Keyword: auditor industry specialization, accrual earnings management, regulation no. 17/PMK.01.2008 concerning public accountant service